FUNGSI SIWOL BAGI KEHIDUPAN SUKU NGALUM - Maryone, Rini (BALAI ARKEOLOGI PAPUA, 2010)
The trading activity in Indonesia, particularly in ancient Papua has depicted that the medium of exchange become an important thing in transaction activity. It can be inferred that the trading activity in the past was also done by the tribes who lived in the mid-mountain like Ngalum community. The medium of exchange that they used was siwol/seashell. The use of siwol, as a medium of exchange, nowadays has changed for it has been influenced by official exchange medium (rupiah). Thus this currency has become the official exchange medium for Ngalum Community.